2019
DOI: 10.31234/osf.io/jqfwp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shall I trust you? From child human-robot interaction to trusting relationships

Abstract: Studying trust within human-robot interaction is of great importance given the social relevance of robotic agents in a variety of contexts. We investigated the acquisition, loss and restoration of trust when preschool and school-age children played with either a human or a humanoid robot in-vivo. The relationship between trust and the quality of attachment relationships, Theory of Mind, and executive function skills was also investigated. No differences were found in children’s trust in the play-partner as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…A recent review of the literature by Marchetti et al (2018) showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008 ; Itakura et al, 2008 ; Moriguchi et al, 2011 ; Kannegiesser et al, 2015 ; Okanda et al, 2018 ; Di Dio et al, 2019 ; Wang et al, 2020 ; Manzi et al, 2020a ) and developmental robotics (DR; De La Cruz et al, 2014 ; Cangelosi and Schlesinger, 2015 , 2018 ; Lyon et al, 2016 ; Morse and Cangelosi, 2017 ; Vinanzi et al, 2019 ; Zhong et al, 2019 ; Di Dio et al, 2020a , b ). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people’s behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of the literature by Marchetti et al (2018) showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008 ; Itakura et al, 2008 ; Moriguchi et al, 2011 ; Kannegiesser et al, 2015 ; Okanda et al, 2018 ; Di Dio et al, 2019 ; Wang et al, 2020 ; Manzi et al, 2020a ) and developmental robotics (DR; De La Cruz et al, 2014 ; Cangelosi and Schlesinger, 2015 , 2018 ; Lyon et al, 2016 ; Morse and Cangelosi, 2017 ; Vinanzi et al, 2019 ; Zhong et al, 2019 ; Di Dio et al, 2020a , b ). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people’s behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have further shown that already from three years of age, children fairly differentiate a human from a robot in terms of mental abilities ( Di Dio et al, 2020a ), although younger children appear to be more inclined to anthropomorphize robots compared to older children. This effect may be due to the phenomenon of animism, particularly active at three years of age ( Di Dio et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of course important to know whether these new technological tools, in their various forms, are welcomed by the potential users, both in the clinical and in an at-home setting. To interact with someone, or something, from early in life we need to trust in the relationship ( Di Dio et al., 2020a , Di Dio et al., 2020b ) and in the efficacy of the help that the other, person or thing, can provide us. Our health is everything after all and we want to put it in good hands.…”
Section: Robots and Adultsmentioning
confidence: 99%
“…The individual undertakes a path in which the “known social other”/“unknown social other” dichotomy acts as an organizer of beliefs and attitudes, thus contributing to the construction of the Self as a distinct and separate entity from the Other. From a sensorineural point of view, the human baby is equipped to recognize and trustfully orient herself/himself toward primary figures of care and protection; it is precisely on this basis that trust is built in others and ourselves (Di Dio et al, 2019 , 2020a , b ; Manzi et al, 2020a , b ). The so-called “anguish of the stranger” (Spitz, 1945 ; Schaffer, 1966 ) emerges around 8 months of age.…”
mentioning
confidence: 99%